FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA APARATUR DI DEPUTI BIDANG PERSIDANGAN SEKRETARIAT JENDERAL DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA - Muhammad Dimyati Sudja; Heru Dian Setiawan (Ilmu dan Budaya, 2021)
This research is based on the phenomenon of the low performance of the employees in the Deputy for the Field of Court, Secretary General of the DPR RI. This of course cannot be tolerated because the Deputy for the Field of Court related to the task of carrying out the preparation of policy formulations, coaching, and implementation of court support to the DPR RI, is also a challenge and a tough task for the Secretary General of the DPR RI to reduce or even eliminate the negative image of the DPR RI in the eyes of Public. Using a qualitative approach, and using the theory of Dwiyanto (2005; 16), this study aims to determine the factors that influence the performance of the officials at the Deputy for Session of the Secretariat General of the People's Representative Council of the Republic of Indonesia. The conclusion is quite good in increasing the role and function of the People's Representative Council of the Republic of Indonesia, but there are still constraints on the factors of productivity, service quality, responsiveness, responsibility, and accountability